Smoking and Smoking Cessation Among Criminal Justice–Involved Older Adults. (March 2019) - Ahalt, Cyrus; Buisker, Timothy; Myers, Janet; Williams, Brie
Background: In jails and prisons worldwide, older adults are among the fastest growing demographic groups. Criminal justice–involved populations smoke tobacco at high rates. Older adults are also disproportionate smokers and have more difficulty quitting smoking than other age groups. Yet, little is known about tobacco use or knowledge and attitudes toward smoking cessation among the growing population of incarcerated older adults. Methods: A descriptive, cross-sectional survey study of 102 adults aged 55 years or older recently incarcerated in an urban jail using items from the Global Adult Tobacco Survey (GATS). Results: More than 70% of participants reported being current smokers despite strong knowledge (95%) of the connection between smoking and serious illness. More than half of current smokers reported a past failed quit attempt (62%) and/or said they would like to quit (60%). Conclusions: High rates of tobacco use in this population suggest that correctional institutions represent a critical site for the delivery of appropriate smoking cessation interventions to older adults, including integrated treatment approaches for those with co-occurring behavioral health diagnoses.